Photocatalysis and adsorption coupling in S-scheme K and P doped g-C3N4/GO/MgFe2O4 photocatalyst for enhanced degradation of Congo red dye - Rohit Kumar; Aftab Aslam Parwaz Khan; Anita Sudhaik; Sonu Sonu; Savas Kaya; Pardeep Singh; Pankaj Raizada; Mohie E M Zayed; Muhammad Nadeem Arshad; Khalid A Alzahrani (Nano Express, 2025)
Photocatalysis is an environmentally friendly approach for harnessing solar light to degrade pollutants. This study investigates the degradation of Congo red (COR) dye by a visible light-active photocatalyst, with a primary focus on the efficiency and reusability of the photocatalytic material. We synthesized phosphorus- and potassium-doped graphitic carbon nitride photocatalysts attached to graphene oxide and MgFe _2 O _4 (KPCN/GO/MgFe _2 O _4 ). Doping graphitic carbon nitride enhanced light absorption, while graphene oxide improved the adsorption properties. The addition of magnetic MgFe _2 O _4 enhanced charge separation and reusability. The KPCN/GO/MgFe _2 O _4 composite was analyzed using a range of techniques. The activity of the synthesized materials for Congo red (COR) dye degradation was analyzed under visible light. The photocatalytic activities of bare, binary, and ternary photocatalysts were compared, and KPCN/GO/MgFe _2 O _4 exhibited the highest photoactivity among all. The KPCN/GO/MgFe _2 O _4 photocatalyst (60 mg) showed a 76% removal efficiency for 5 × 10 ^−6 M Congo red within 60 min, which was 2.5 times higher than that of pure graphitic carbon nitride. The ·OH and ·O ^2- were the major reactive species during COR photodegradation. The photocatalyst also displayed good reusability after five cycles, enhancing its overall effectiveness.